: Evolución histórica de las normativas de diseño sismo resistente en América Latina. casos de estudio: Colombia, Ecuador, Perú y Chile - Quinatoa Martínez, Jhonny Gabriel (2022)
Ecuador, Peru and Chile are located in the Pacific Ring of Fire. This location makes them countries with a high level of seismic hazard. In the mid-twentieth century, the response of these countries to these natural events was the creation of construction standards for the earthquake-resistant design of structures. Seismic hazard codes were primarily based on the application of a force at the base of the structure to simulate the design earthquake. This hypothesis was raised in various international codes and adapted to the needs of each territory. This document shows the historical evolution of the regulations referring to seismic hazard, earthquake resistant design, of Colombia, Ecuador, Peru and Chile, analyzing the reason for its creation, updating and what were the main variables when calculating the force exerted on it. the structures. This objective was achieved by searching for information in official documents, scientific articles, among others, to later create a chronological matrix of historical events and changes that each reform went through. As a result of the investigation, the number of updates of each regulation, the reason for the reform and the evolution of the calculation process of the base shear, reactive load and floor drifts are obtained. In addition, the main challenges and updates that should be faced and implemented for the creation of the new codes are presented.